Advanced reliability modeling : proceedings of the 2004 Asian International Workshop (AIWARM 2004) : Hiroshima, Japan, 26-27 August 2004 - Dohi, Tadashi; Kaio, Naoto, 1953-; Yun, Won Young (Journal of quality in maintenance engineeriing ;, 2005)
This e-book contains selected papers invited/presented in the Asian International Workshop on Advanced Reliability Modeling (AIWARM) which was held in Hiroshima, Japan, August 26-27, 2004. 78 papers from Asian and European area were presented at the workshop. This e-book is intended to share the ideas and results from the workshop with more reliability researchers and practitioners. Various and promising research topics are included; maintenance problems in shock models, replacement model with spare part provisioning, analysis of system operating data with fuzzy set, new algorithms in redundan.